Analisis Sentimen Masyarakat Terhadap Kinerja Trans Semarang Menggunakan Metode Random Forest - Fachreza, Rizqi; Handoko, Widiyanto Tri (STMIK Banjarbaru, 2024)
Opinion from the public on the performance of Trans Semarang transportation that has been widely discussed on social media X, resulting in many pros and cons. Sentiment analysis comes as a way to understand public opinion, examining the opinions and attitudes of individuals towards an object. individual attitudes towards an object. By using an algorithm methodology, namely Random Forest in classifying data to determine the accuracy of the data to determine the accuracy of the level of sentiment value of X users towards Trans Semarang performance. performance of Trans Semarang. This research uses a dataset taken with keyword